2017
DOI: 10.1093/mnras/stx2813
|View full text |Cite
|
Sign up to set email alerts
|

Polarization light curve modelling of corotating interaction regions in the wind of the Wolf–Rayet star WR 6

Abstract: The intriguing WN4b star WR6 has been known to display epoch-dependent spectroscopic, photometric and polarimetric variability for several decades. In this paper, we set out to verify if a simplified analytical model in which Corotating Interaction Regions (CIRs) threading an otherwise spherical wind is able to reproduce the many broadband continuum light curves from the literature with a reasonable set of parameters.We modified the optically thin model we developed in Ignace et al. (2015) to approximately acc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…WR 6 is still considered to be single; the polarimetric and photometric variability was rediscussed by St-Louis et al (2018) and attributed to CIRs.…”
Section: The Sample Of Wn Starsmentioning
confidence: 99%
“…WR 6 is still considered to be single; the polarimetric and photometric variability was rediscussed by St-Louis et al (2018) and attributed to CIRs.…”
Section: The Sample Of Wn Starsmentioning
confidence: 99%
“…Schmutz & Koenigsberger 2019) or CIRs (e.g. Moffat et al 2018;St-Louis et al 2018). Harries et al (1999) measured the ISP using a different method from ours, and found a very different result of P max = 0.47 ± 0.02% at θ 0 = 164 ± 2 • .…”
Section: Intrinsic Polarizationmentioning
confidence: 53%
“…In view of the fact that the polarization curves we obtain using MCRT for CIRs in a spherical wind are quite different from those obtained using analytical models, the fits of the observations of the WR star WR6 presented in St-Louis et al (2018) need to be re-done. The fact that our MCRT curves have a much smaller amplitude and, depending on the optical depth of the wind, have peaks that are shifted compared to those obtained with the analytical models will certainly result in different output parameters, such as the density contrast or the opening angle of the CIR and perhaps even in a different orientation of the stellar axis with respect to our line-of-sight.…”
Section: Mcrt Cir Polarization Curves For a Range Of Densitiesmentioning
confidence: 99%
“…We also present error estimates for different wind densities introduced by varying the random number generator seed. In Section 4 we compare our polarimetric calculations to those obtained both for the optically thin (Ignace et al 2015) and thick (St-Louis et al 2018) limits. Finally, in Section 5 we present a parameter study for polarization and light curve calculations including a CIR and an associated bright gaussian spot.…”
mentioning
confidence: 99%
See 1 more Smart Citation